PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKIF BIOLOGI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP - Gede Ari Yudasmara; Desi Purnami (Jurnal Pendidikan dan Pengajaran, 2015)
ABSTRACT: Developing Interactive Instructional Media in Biology to Improve Junior High School Students’ Achievement. This study aimed to produce interactive instructional media inter-active which is practical, and effective. This research was a research and development, which was-held in SMP Negeri 3 Bangli Kintamani to the class VIIIA in the Odd semester of the school year 2014/2015. The subjects were Biology teacher and eighth grade students of class VIIIA. The data were analyzed using descriptive analysis related to aspects of practicality and effectiveness through a questionnaire and Biology achievement test. The result shows that 1) the media that was developed has fulfilled the criteria of practicality based on the average score of the response of teachers to 3.73 (categorized positive) and the students' responses 3.5 (categorized very positive) and 2) interactive instructional media of Biology has accomplished the criteria of effectiveness because it has reached the learning outcomes of the test scores of students who achieved an average of 79.04 above KKM (the minimum criteria of mastery) from previously determined 72, and the percentage of students achieving the minimum criteria of mastery is 95.83%. Keywords: instructional media, learning achievement, quality of media ABSTRAK:Pengembangan Media Pembelajaran Interakif Biologi untuk Meningkatkan Hasil Belajar Belajar Siswa SMP. Penelitian ini bertujuan untuk menghasilkan media pembelajaran interaktif biologi yang praktis, dan efektif. Penelitian ini merupakan penelitian pengembangan, yang dilaksanakan di SMP Negeri 3 Kintamani Bangli, pada kelas VIIIA semester Ganjil tahun pelajaran 2014/2015. Subjek penelitian ini adalah guru Biologi dan siswa kelas VIIIA SMP Negeri 3 Kinta-mani. Teknik analisis data menggunakan analisis deskriptifyang berkaitan dengan aspek kepraktisan dan efektivitas melalui angket dan tes hasil belajar biologi siswa. Hasil analisis data menunjukkan bahwa 1) media pembelajaran yang berhasil dikembangkan telah memenuhi syarat kepraktisan ber-dasarkan rata-rata nilai respon guru 3,73 (terkategori positif) dan respon siswa 3,5 (terkategori sangat positif) dan 2) Media pembelajaran interaktif biologi ini telah memenuhi syarat keefektivan karena telah berhasil mencapai nilai tes hasil belajar siswa yang mencapai rata-rata 79,04 diatas KKM yang ditetapkan yaitu 72, dan persentase tingkat ketuntasan minimal siswa mencapai 95,83%. Kata-kataKunci: hasil belajar siswa, kualitas media, media pembelajaran